I am an elephant:Read more about me (Mind to Mind)
I Am an Elephant: Read More About Me is a 16-page board book from Mind To Mind Publishing, part of their Read More About Me series. Aimed at children aged 2 to 5, this book introduces young readers to the life and characteristics of elephants through simple text and vibrant illustrations. It covers aspects such as where elephants live, what they eat, and how they move, providing a fun and educational experience for toddlers and preschoolers.
I Am an Elephant: Read More About Me is a toddler-friendly board book from Mind To Mind Publishing$1 (Bs Read More About Me series, designed for children aged 2 to 5. Featuring simple, clear language and colorful illustrations, the book introduces young readers to elephants$1 (Btheir habitat, diet, physical characteristics, and behavior. Its sturdy board book format is ideal for small hands, making it perfect for early childhood education, read-aloud sessions, and fostering an early interest in animals and nature. The book supports vocabulary development and provides foundational knowledge about one of the largest and most fascinating animals in the wild.s
Keywords: Animal behavior $1 (BIntroductory levels; Early childhood education